Development of starch/chitosan nanoparticle nanocomposite films with antibacterial properties - Ahmad Shapi’i, Ruzanna (2018)
The application of biopolymers as food packaging material are limited due to the poor desired properties. Incorporation of chitosan nanoparticle (CNP) into biopolymer films can improve the desired properties of the films which include mechanical, thermal, barrier, and antibacterial properties. Thus, this work is directed towards developing starch/CNP films with improved properties. CNP was first synthesized using different concentrations of chitosan 0.3, 0.6, 0.9, 1.2, 1.5, 1.8, and 2.1% w/v) and the average particle size of CNP was measured via DLS and TEM. DLS analysis revealed that the particle size of CNP increased from 46.76 to 225.33 nm (4-fold increment) with the increase in initial concentration of chitosan. The average particle size of 0.9% w/v CNP measured via DLS was 106.34 nm while that measured via TEM analysis was 53.93 nm. Note that, TEM provides the actual size of CNP in dehydrated state whereas DLS provide hydrodynamic size in hydrated state hence TEM was more accurate to measure the size of the produced CNP. Starch/CNP films were produced using solution casting method with varying concentration of CNP (5, 10, 15, 20, 25, 30, 35% w/w of solid starch). The mechanical, thermal, barrier, and optical properties of the starch/CNP films (average thickness: 0.07 mm) were characterized. Addition of 15% w/w CNP into starch films improved the tensile strength from 1.12 to 10.03 MPa (7.96-fold increment) and elongation at break from 67 to 90.77% (0.35-fold increment). This was due to the good interfacial interaction formed between starch and CNP thus produced a compact and rigid structure of the film. Improvement in the structure of the films led to the enhancement in the thermal stability of the film whereby residue of starch film increased from 7.91% to 23.48% (2-fold increment). Furthermore, reduction in the water vapor permeability from 1.1 x 10-11 g/Pa h m to 0.63 x 10-11 g/Pa h m (4-fold increment) and oxygen permeability from 7.38 x 10-3 cm3/Pa.day.m to 3.59 x 10-3 cm3/m.day.Pa (0.51-fold increment) of the film was observed. Meanwhile, addition of CNP slightly increased the opacity of 15% w/w starch/CNP films from 8.07 to 14.67 due to the presence of CNP within the starch matrix that hinder the light transmission pass through the film. The antibacterial properties of starch/CNP films were evaluated via disc-diffusion analysis to observe the inhibition zone of the films. Starch/CNP films incorporated with 15% and 20% w/w CNP exhibited clearer inhibitory zone for gram-positive bacteria (B. cereus, S.aureus) compared to gram-negative bacteria (E. coli, S. typhi). The application of starch/CNP films was demonstrated on the cherry tomatoes whereby the microbial growth in cherry tomatoes was evaluated during 10 days storage period. It was found that the 15% w/w starch/CNP film was more efficient to inhibit the microbial growth in cherry tomatoes (7 x 102 cfu/mL) compared to starch film (2.15 x 103 cfu/mL), thus confirmed the antibacterial properties of the starch/CNP film. In conclusion, starch/CNP film developed in this study exhibit improved properties and has the potential to be used as food packaging material.